PENERAPAN STRATEGI BELAJAR MURDER (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VIII.3 SMP NEGERI 25 PEKANBARU TAHUN AJARAN 2013/2014 - Vivi Ardina; Agus Baskara (PEKA, 2015)
PENERAPAN STRATEGI BELAJAR MURDER (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VIII.3 SMP NEGERI 25 PEKANBARU TAHUN AJARAN 2013/2014 VIVI ARDINA AGUS BASKARA ABSTRACT From the observations and interviews with teachers of SMP 25 IPS Pekanbaru, there are some problems that occur in social studies classes at SMP 25 Pekanbaru VIII.3 namely; (1) the motivation of students to follow the learning is still not visible, (2) there are many students who forget the previous lesson, the teacher continued after subsequent material, (3) active in work on the problems-exercises in the learning process is still lacking, (4) students rarely ask questions, even if teachers request that students often ask if there are things that have not or do not understand, (5) lack of interest to participate in all social studies, (6) is still a lack of education Applying IPS values ​​in everyday life. Given the above problems, the researcher perform actions through the application of learning strategies MURDER to improve student learning outcomes in social studies learning in the classroom VIII.3. The instrument used in this research work lenbar tests and teacher activity sheets and sheets of student learning activities in a descriptive analysis of the data. The results of this study showed increased student learning outcomes. Absorption of students in the first cycle with an average 79.25 % and 86.37 % second cycle. In the learning activities of students during the learning process of the first cycle with an average 55.6 % increase in the second cycle is 73%. Based on the results of this study concluded that the application of learning strategies MURDER can improve student learning outcomes in social studies VIII 3 in SMP 25 Pekanbaru. Keywords: MURDER learning strategy, learning outcomes.